Notificação da violência doméstica infanto-juvenil da rede pública de ensino de Fortaleza- Ce - Rocha, Fabíola de Castro (2010)
The directions considered in the Statute for Protection of the Child and the Adolescent with respect to guarantee of the rights and integral protection to infancy and youth place the school and the establishments of health as protagonists in the identification of children and adolescents in situation of risk for domestic violence and attribute to the educator and to the professional of health the task to recognize and to communicate to the protection agencies infancy and youth, as form of preventing the damages the development human being in this stage of the life. Where it almost weighs the advances reached in twenty years of validity of the Statute for Protection of the Child and the Adolescent, still it prevails, in the current days, a resistance on the part of these professionals in assuming its parcel of responsibility in the confrontation of the domestic violence. Under this optics, the research was carried through that had as objective to identify the attitude of the educators of the municipal net of education of Fortaleza-CE, how much to the notification of identified cases suspicious or of the Child and Adolescent domestic violence in its daily one of work. The action methodology constituted in the distribution of daily pay-structuralized questionnaires the educators of 40 institutions of education of the six Regional Executive Secretariats of Fortaleza, Together with the questionings they had been you deliver the informed consent form free and clarified, that make possible to the educator the decision freedom how much the participation. The gotten results, from 454 answered questionnaires (80.5%), had been inserted in a data base, and later systemize in tables and graphs for analyses. The quarrel was carried through collating the results gotten with theoretical recitals of researchers of the area of the domestic violence. It was observed that referring to a bigger perception of the violence associated with the partner-demographic data of the educators, they had been evidenced as favorable aspects, the prevalence of the feminine sex (p=0,002), in the band of the 2 5 wages of reference (p=0,015), considering only its familiar income, beyond the double hours of working with pupils in different age group (p<0,001). Considering the distribution it enters the six Regional Executive Secretariats of Fortaleza, demonstrated a strong diversity how much to the perception of the occurrences. The “externalização” on the part of the child or vitimizado adolescent, it was the main manifestation perceived for the educators in the identification of bad-treatments (71,2%). Still in regards to the perception, the recklessness was the form that more excited recognition (34,7%), followed of the physical (30,0%), psychological violence (24,6%) and finally, the sexual violence (10,7%). How much to the procedure of interruption of the vitimização, the sexual violence was the one that received greater intervention and communication. It was still evidenced, practical of the attempt of “solution the caretaker” in the resolution of the cases evidenced in the schools/searched day-care centers, with story of the same ones to the fellow workers, the direction of the school or the proper family of the victim, without the had provocation to the competent agencies. The attitude of the educators ahead of the bad-treatments certainly elapses of a complexity of sociological factors and cultural values that they efficiently need to be worked. Stand out-section in this aspect, the fact of few professionals to have participated of qualification on the subject of the domestic violence, the spite of the unanimous story of interest in the update on the subject. Thus the carried through reflections, stand out that it is of basic importance that if it reflects on knowing them and practical of the involved professionals in the basic and basic educational orientation, in the direction to promote and to make possible the enrollment of this professional in the development and integral protection of the child and adolescent, being thus fulfilled the social paper, pedagogical politician and.